Aurora-A drives sorafenib resistance by scaffolding stress granule assembly via phase separation - Lingyu Kong; Fumei Zhong; Fazhi Yu; Ting Wang; Gang Wang; Yu Bai; Han Xia; Zihang Pan; Mingxue Liu; Yan Zhang; Rui Feng; Jiahai Zhang; et al. (Proceedings of the National Academy of Sciences, 2026)
The mitotic kinase Aurora-A is frequently overexpressed in cancers and contributes to tumor progression and therapy resistance, yet the mechanisms underlying its role in drug resistance remain unclear. Here, we show that sorafenib treatment triggers Aurora-A phase separation, leading to its recruitment into stress granules (SGs), membraneless organelles that promote cancer cell survival. Aurora-A facilitates robust SGs assembly, thereby conferring sorafenib resistance. Mechanistically, upon sorafenib-induced SGs formation, Aurora-A binds RNA via positively charged lysine/arginine residues within its intrinsically disordered region (IDR). Mutating these K/R residues with IDR of Aurora-A disrupts its RNA binding, impairs SGs assembly, and resensitizes cancer cells to sorafenib. Together, our work identifies Aurora-A as a kinase-activity-independent, RNA-binding scaffold essential for stress-adaptive biomolecular condensation, revealing a druggable phase-separation axis distinct from canonical Aurora-A kinase signaling.